Evaluation of bone regeneration in mandible large defect using undifferentiated adipose stem cells loaded on gelatin carrier: An animal model case study - Ali Hossein Mesgarzadeh; Islam Nasiri; Seyedhosein Jarolmasjed; Mehran Naghibi; Hajar Shafaei (Tabriz University of Medical Sciences, 2021)
Background. Large mandibular defects are considered difficult reconstructive challenges for oral and maxillofacial surgeons. Cell therapy, as an alternative technique, might increase the speed of bone regeneration. This study aimed to investigate bone regeneration in large defects of dog mandibles using allogenic adipose-derived stem cells on gelatin foam as a cell carrier. Methods. The tissue engineering phase consisted of the sampling of adult dogs' adipose tissue that can easily be isolated from adipose stem cells (ASCs) of the dogs, ASCs were cultured in Dulbecco's Modified Eagle's Medium (DMEM, Gibco, USA) with low glucose, containing 10% fetal bovine serum (FBS) (Sigma, USA) and 1% penicillin-streptomycin (Gibco, USA), with the characterization of dog ASCs and gelatin-transplanted ASCs. Six dogs were included in this experimental study in the next step and randomly assigned to the treatment and control groups. The samples in both groups underwent surgery under general anesthesia to create uniform 3-cm bony defects. The samples in both groups were reconstructed with titanium reconstruction plates and screws. A large bone gap filled with ASCs (5×106 ) was seeded on gelatin (ASCs) in the treatment group. In the control group, bony defects were filled with a cell delivery carrier without ASCs. Six months after transplantation, the animals' mandibles were evaluated by CT scan imaging, and the results were quantified through the Hounsfield unit (HU). The data were analyzed with t-test. Results. Before transplantation, the nature of the stem cells was confirmed by the expression of CD44 and CD105 cell markers at 71.9% and 89.3%, respectively, and a lack of the CD45 cell marker expression at 2.2%. Evaluation of CT scan images showed significantly higher bone repair in the ASCs group (920.25±572.92 HU) than in the control group (-94.746± 08.42). Conclusion. The bone regeneration of the ASCs group was significantly higher than that in the control group.